Venlafaxine increases aromatization, reduces apical V-ATPase in clear cells and induces increased number of mast cells and smooth muscle cells death in rat cauda epididymis - da Silva, André Acácio Souza [UNESP]; de Santi, Fabiane; Hinton, Barry T.; Cerri, Paulo Sérgio [UNESP]; Sasso-Cerri, Estela [UNESP] (Elsevier, 2023)
Depressive disorders (DD) have affected millions of people worldwide. Venlafaxine, antidepressant of the class of serotonin and norepinephrine reuptake inhibitors, has been prescribed for the treatment of DD. In rat testes, venlafaxine induces testosterone (T) aromatization and increases estrogen levels. Aromatase is a key enzyme for the formation of estrogen in the epididymis, an essential organ for male fertility. We investigated the impact of serotonergic/noradrenergic venlafaxine effect on the epididymal cauda region, focusing on aromatase, V-ATPase and EGF epithelial immunoexpression, smooth muscle (SM) integrity and mast cells number (MCN). Male rats were distributed into control (CG; n = 10) and venlafaxine (VFG, n = 10) groups. VFG received 30 mg/kg b.w. of venlafaxine for 35 days. The epididymal cauda was processed for light and transmission electron microscopy (TEM). The expression of connexin 43 (Cx43) and estrogen alpha (Esr1), adrenergic (Adra1a) and serotonergic (Htr1b) receptors were analyzed. Clear cells (CCs) area, SM thickness, viable spermatozoa (VS) and MCN were evaluated. Apoptosis was confirmed by TUNEL and TEM. The following immunoreactions were performed: T, aromatase, T/aromatase co-localization, V-ATPase, EGF, Cx43 and PCNA. The increased Adra1a and reduced Htr1b expressions confirmed the noradrenergic and serotonergic venlafaxine effects, respectively, corroborating the increased MCN, apoptosis and atrophy of SM. In VFG, the epithelial EGF increased, explaining Cx43 overexpression and basal cells mitotic activity. T aromatization and Esr1 downregulation indicate high estrogen levels, explaining CCs hypertrophy and changes in the V-ATPase localization, corroborating VS reduction. Thus, in addition to serotonergic/noradrenergic effects, T/estrogen imbalance, induced by venlafaxine, impairs epididymal structure and function.
Keywords: Antidepressant; Apoptosis; Clear cells; Immunofluorescence; Mast cells; SNRI